On A Comparative Study of Direct Solution Methods of the Discrete Poisson’s Equation on A Rectangle - Adekanmbi, Damilola Victoria (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The solution of systems of algebraic equations arising from the 5-point discretization of Poisson’s equation on a rectangle with Dirichlet boundary conditions is analyzed by direct solution methods. Special emphasis is given for block direct methods, such as block elimination, block decomposition and block cyclic reduction methods. For this purpose block elimination algorithms, orthogonal block decomposition algorithms, cyclic odd even reduction method, (CORF) algorithm and Buneman version of the CORF algorithm is also studied. A test problem is constructed for the Laplace equation and solved by these block methods for the mesh size 1 4 h  . Comparisons are given based on the computational complexity of the methods. Keywords: Block elimination methods, block cyclic reduction method, block decomposition methods, Thomas algorithm, discrete Poisson’s equation, 5-point scheme.

ÖZ : Poisson denkleminin dikdörtgen üzerindeki Dirichlet sınır değer probleminin 5-nokta çözümlemesi ile elde edilen cebirsel denklem takımlarının çözümü doğrudan yöntemler ile incelendi. Blok yoketme yöntemleri, blok ayrıştırma yöntemleri, ve blok döngüsel indirgeme yöntemleri gibi blok doğrudan yöntemlere özel önem verildi. Bu amaç doğrultusunda blok yoketme algorithmaları, dik blok ayrıştırma algorithmaları, tek çift döngüsel indirgeme metodu, (CORF) algorithması ve Buneman versiyonu çalışıldı. Laplace denklemi için bir test proplemi oluşturuldu ve adım büyüklüğü 1 4 h  için verilen yöntemler ile çözüldü. Karşılaştırmalar yöntemlerin hesaplama karmaşasına göre verildi. Anahtar kelimeler: Blok yoketme yöntemi, blok döngüsel indirgeme yöntemi, blok ayrıştırma yöntemi, Thomas algorıthması, Poisson denklemi, 5-nokta şeması.
Master of Science in Applied Mathematics and Computer Science. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2016. Supervisor: Assist. Prof. Dr. Suzan Cival Buranay.
Keywords: Mathematics; Applied Mathematics and Computer Science; Algebraic Equations - Solutions Systems; Equations - Numerical solutions; Block elimination methods; block cyclic reduction method; block decomposition methods; Thomas algorithm; discrete Poisson’s equation; 5-point scheme